Urgensi Kenaikan Tarif Pajak Pertambahan Nilai Berdasarkan Asas Kepentingan Nasional - Deyola Agasie; Rahmi Zubaedah (Faculty of Law Hang Tuah University, 2022)
Value added tax (VAT) has increased to 11% as of April 1, 2022, this certainly raises pros and cons from various levels of society. The increase in the tax rate is in accordance with the mandate as stated in regulation concerning Harmonization of Tax Regulations. However, to increase a tax rate in the midst of the decline in the Indonesian economy as a result of the Covid-19 Pandemic is a question, so this study aims to identify how the urgency of the value added tax has increased and its impact on the country and society. In solving a problem, the author uses normative juridical research methods, with statute approach. The data obtained through literature study techniques. The results of this study show the urgency of increasing the value-added tax rate and its impact based on the principle of national interest.